Surface analysis of alumina ceramic exposed to shock waves produced by plasma expander. (March 2015) - Mota, R P; Campos, E; Santos, C N; Lucena, E F; Machida, M; Melo, F C L
Abstract: Material surface treatment by plasma expander is relatively recent. Plasma expander is based on the inverse pinch effect. The shock waves produced by plasma expander may also promote modifications in ceramic materials exposed to the expander. These modifications are mainly made by ablation phenomenon. This work was intended to verify the shock wave effects on the ionic ceramic samples with high dielectric constant. The alumina ceramic samples were formed by both uniaxial and isostatic pressing methods and sintered at 1650 °C. They were also produced with addition 0.15 wt% of MgO in order to obtain a high densification. The ceramic samples were divided in groups and exposed to 700, 1000 and 1440 pulses during 20 min. These pulses were generated by nitrogen plasma expander at 13.0 Pa and 6 kV. After plasma exposure, there was an increase in roughness parameter values of Al2 O3 ceramic surface. The treatment by plasma expander did not modify the hydrophilic characteristic of the alumina ceramic samples. The results of hardness test presented no significant changes on hardness mean values.